The cost of immigrants' occupational mismatch and the effectiveness of postarrival policies in Canada - Yigit Aydede; Atul Dar (IZA Journal of Migration, 2016)
Using the 2006 Census, we create a continuous index that quantifies the relatedness between 1375 fields of study and 520 occupations for native-born workers and use it as the benchmark reflecting the "common" matching quality in Canadian labor markets that internationally educated immigrant workers could achieve in the long run. This allows us to approximate the cost of the occupational mismatch of immigrants by estimating the change in their earnings had they been distributed identically to the native born in terms of relatedness. Although the results show a significant and persistent poor matching quality for foreign-educated immigrants, their relative underutilization cost is negligible.
Keywords: J6; J15; J61; 330; Occupational mismatch; Relatedness; Underutilization; Immigration; Wage gap